Wind power renewable energy generation to reduce Cost and the greenhouse effect - Pozo, Hamilton; Soares, Washington Luiz Pereira; Akabane, Getulio Kazue (Archives of Business Research, 2020)
The objective of this research is to analyze and provide economic bases for the use of wind energy, replacing the thermals plants in process of cost reduction, their positive impact on the economy and the environment. The energy obtained through the force of the winds is one of the oldest of the energies known and used by man. This conception of energy production was again evaluated and tested more objectively after the 1980s, especially in the USA and Europe with strong support from ERDA-Energy Research and Development Administration in the development of special turbines to capture energy from the winds and make it economically viable and sustainable. Experiments show that the use of wind energy as an economically and ecologically correct alternative for use in small and large power plants and reduce climate change.)